Holistic Approach for Creating Environmentally Friendly Campus - Andoko, Andrey; Prastomo, Niki (Journal of Sustainability Perspectives, 2021)
To achieve an environmentally friendly campus, UMN operates gas engine generator with co-generation system. Waste heat from generator powers absorption chiller for air conditioning. UMN benefits clean energy sources, reduced pollution, and energy saving. The next phases rely on energy consumption reduction by applying passive design. Two towers were designed with double-skin facade. The perforated aluminum panel reduces solar heat gain on the building wall while still allows sunlight into the room for natural lighting. Lower room temperature will reduce cooling load, which will save energy. Combined with energyefficient appliances and natural air ventilation for corridors and open space, this concept saves more than half of energy consumption. Both towers were awarded the first and second winners of ASEAN Energy Award in 2014 and 2019. Various trees have been planted and produce oxygen to supply fresh air to create comfortable studying environment without air conditioning. To reduce carbon footprint, UMN provides shuttle bus and bike-sharing service. A holistic approach is implemented by recycling and conserving water with sewage water treatment and infiltration wells surrounding the campus. As part of the sustainability program, UMN has also utilized solar energy.